(untitled) (Edad Media. Revista de Historia, 2017)
This paper compares the ecclesial reality of the six major cities of the archbishopric of Toledo (Toledo, Talavera, Madrid, Guadalajara, Ciudad Real and Alcaraz) in the late Middle Ages. In order to do that, it relies on an interesting source: the Libro de Beneficios del Arzobispado de Toledo, put together in 1501 at the request of Cardinal Cisneros. The book provides extensive information about the “religious equipment” of those cities, the number of parishes, the existing benefices and their economic value.